2019
DOI: 10.1021/acs.chemmater.9b03864
|View full text |Cite
|
Sign up to set email alerts
|

Fractal-in-a-Sphere: Confined Self-Assembly of Fractal Silica Nanoparticles

Abstract: Fractal objects such as snowflakes and trees are ubiquitous in nature. However, fractal nanoparticles with uniform morphology and controllable structures are difficult to make. Herein, using a fractal-in-a-sphere strategy, we report the confined self-assembly of fractal silica nanoparticles with tunable fractal generations and uniform sizes. One advantage of controllable fractal generations has been demonstrated in enzyme delivery for parasite oocyst control. The fractal silica nanoparticles exhibited better o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 50 publications
(78 reference statements)
0
25
0
Order By: Relevance
“…Recently, Fu and co‐authors reported the synthesis of MSNs with tree‐branch‐like morphology: fractal silica nanoparticles with tunable fractal generations and uniform particle sizes (Figure 14 a–f) [28] . In this synthesis, TEOS, 3‐aminophenol (AP)/formaldehyde (F), and ethylenediamine (EDA) were used in the Stöber system.…”
Section: Synthesis Structures and Formation Mechanisms Of Dmsnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fu and co‐authors reported the synthesis of MSNs with tree‐branch‐like morphology: fractal silica nanoparticles with tunable fractal generations and uniform particle sizes (Figure 14 a–f) [28] . In this synthesis, TEOS, 3‐aminophenol (AP)/formaldehyde (F), and ethylenediamine (EDA) were used in the Stöber system.…”
Section: Synthesis Structures and Formation Mechanisms Of Dmsnsmentioning
confidence: 99%
“…the Webo fS cience under the keywords "dendritic mesoporous silica" or "fibrous mesoporous silica" or "radial mesoporous silica", indicating the growing attention on this type of MSN in recent years.However,there is an ongoing debate on their structures and formation mechanisms,a sr eflected by many terminologies used to describe the structures,s uch as "dendritic", [18][19][20][21][22][23] "dendrimer-like", [24,25] "fibrous", [26] "wrinkle", [27] "radial", [7] "fractal", [28] "chrysanthemum-like", [29] "dandelion-type", [30] "stellate" [31] and "core-cone shaped", [14,32] usually accompanying various proposed assembly mechanisms.T he main reason for the controversy may come from the limitations of the characterization methods to examine these nanoparticles which have complicated pore structures without ordered mesostructures." DMSNs" is the most common name used to describe all those types of MSNs, [7,33,34] even though some of them have clear structure differences.…”
Section: Introductionmentioning
confidence: 99%
“…The low mass‐transfer‐limitation of the precursors in the radial direction favored the radial growth of the resin and silica restricted in the shells. [ 52 ] As a result, large center‐radial pores could be obtained after removing the resin component from the composite spheres. Increasing the NH 3 ·H 2 O concentration could lead to a faster gelation of resin and silica particles and reduce their size.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Fu et al reported a confined self-assembly method for the preparation of fractal silica nanoparticles with tetraethyl orthosilicate (TEOS), 3-aminophenol/formaldehyde, and ethylenediamine (EDA) in a surfactant-free sol-gel system [ 31 ]. The prepared fractal silica nanoparticles have a dendritic structure with large center-radial vertical mesopores.…”
Section: Introductionmentioning
confidence: 99%